Nasza klatwa - Śliwiński, Tomasz (Poland : Ślesicki, Maciej, 2013)
According to legend, the water nymph Ondine placed a curse on her unfaithful lover that prevented him from sleeping. Sleep meant death for him. The film is a personal story about the director, Tomasz Śliwiński and his wife as they learn to live with their newborn son Leo's rare, medical condition called Ondine's curse, scientifically referred to as Congenital Central Hypoventilation Syndrome. It causes the sufferer to stop breathing when he or she falls asleep, and there is no cure. Though the doctor sends the couple home talking of Leo's illness as "a cool challenge", they can hardly get their heads around it. Śliwiński records the hardships endured by he and his wife from the day they bring Leo home from the hospital, through the first sleepless nights, but also the moments of optimism and joy Leo brings into their lives.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films